PROFIL KEMAMPUAN MULTI REPRESENTASI TERHADAP KELOMPOK PRESTASI BELAJASR DAN KECERDASAN MAJEMUK SISWA SMP - S, Sheny Meylida (2013)
Physics is part of Natural Science (IPA) which is considered difficult school subject by students (Angel et al, 2004:2). Because physics requires students to cope with a range of different representations (experiments, graphs, conceptual/verbal descriptions, formulae, pictures/ diagrams) simultaneously and to manage the transitions between these. by Dollin (2002) in ( Ornek et al, 2008:30). Representation capabilities of students affected by the representation format, mastery concept, age and individual differences (Ainsworth, 1999). Influenced by individual differences such as intelligence. This study aims to describe and explain the ability of multi representation profile of the group of academic achievement and students' multiple intelligences. The sample was one of the eighth grade at a junior high school in Bandung, totaling 34 students. Means of collecting data in the form of two types of tests, namely 1) test the ability of multi-shaped representation of 20 multiple-choice items consisting of various representations such as pictures, verbal, data, and mathematical symbols, 2) Test Multiple Intelligences Scale (MIS) is used to determine sequence of the multiple intelligences of each student given before the learning takes place. The results illustrate a) the ability to multi representation profile of the group of student achievement that is, the ability to multi-representation proportional to student achievement, b) the ability of multi representation profile of the multiple intelligences, are as follows: 1) very superior interpersonal intelligence group in answering questions type of graph-verbal problem, 2) logical-mathematical intelligence group excels in the type of data to answer questions about the type-verbal and mathematical image, 3) Group kinesthetic intelligence excels at answering questions verbal-mathematical type, 4) verbal-linguistic intelligence group and excel in answering questions interpersonal verbal-image type, 5) Almost all of superior intelligence in answering the question types-verbal symbols except visual-spatial intelligence. Keywords: Multiple Intelligences, Multiple Representation Fisika merupakan bagian dari rumpun Ilmu Pengetahuan Alam (IPA) yang dianggap sulit oleh siswa (Angel et all, 2004:2). Penyebabnya adalah dikarenakan siswa mengalami kesulitan untuk menguasai representasi-representasi yang berbeda, seperti percobaan, rumus-rumus beserta hitungan, grafik dan penjelasan-penjelasan konsep secara bersamaan, selain itu siswa harus mengelola perubahan diantara representasi-representasi tersebut menurut Dollin (2002) dalam (Ornek et all,2008:30). Kemampuan representasi siswa dipengaruhi oleh format representasi, penguasaan konsep, umur serta perbedaan individual (Ainsworth, 1999). Perbedaan individual diantaranya dipengaruhi oleh kecerdasan. Penelitian ini bertujuan untuk menggambarkan dan menjelaskan profil kemampuan multi representasi terhadap kelompok prestasi belajar dan kecerdasan majemuk siswa. Sampel penelitian adalah salah satu kelas VIII pada suatu SMP negeri kota Bandung, yang berjumlah 34 orang siswa. Alat pengumpul data berupa dua jenis tes, yakni 1) tes kemampuan multi representasi berbentuk pilihan ganda sebanyak 20 butir soal yang terdiri dari berbagai representasi seperti gambar, verbal, data, simbol maupun matematika, 2) Tes Multiple Intelligences Scale (MIS) digunakan untuk mengetahui urutan kecerdasan majemuk masing-masing siswa yang diberikan sebelum pembelajaran berlangsung. Hasil penelitian menggambarkan a) profil kemampuan multi representasi terhadap kelompok prestasi belajar siswa yaitu, kemampuan multi representasi berbanding lurus dengan prestasi belajar siswa, b) profil kemampuan multi representasi terhadap kecerdasan majemuk, adalah sebagai berikut: 1) Kelompok kecerdasan interpersonal sangat unggul dalam menjawab soal tipe soal grafik-verbal, 2) Kelompok kecerdasan logika-matematis unggul dalam menjawab soal tipe data-verbal dan soal tipe gambar-matematis, 3) Kelompok kecerdasan kinestetik sangat unggul dalam menjawab soal tipe verbal-matematik, 4) Kelompok kecerdasan linguistik-verbal dan interpersonal unggul dalam menjawab soal tipe verbal-gambar, 5) Hampir semua kecerdasan unggul dalam menjawab soal tipe verbal-simbol kecuali kecerdasan visual-spasial. Kata kunci : Kecerdasan Majemuk, Multi Representasi